Streptococcus lutetiensis as a cause of calcaneal osteomyelitis, an unusual etiology: a case report - Vela Goñi, Omar Ituriel; Hermida Galindo, Luis Felipe; Pedraza Villarreal, Cesar Fernando; Estrada Cocom, Marian Isabel; López Romo, Alicia Estela (Journal of the Foot & Ankle, 2025)
Streptococcus bovis is a well-known cause of endocarditis and some joint infections, but is not commonly known as a cause of osteomyelitis. One patient suspected of having calcaneus osteomyelitis was analyzed via magnetic resonance imaging and laboratory studies, debridement was performed, and the result was chronic osteomyelitis caused by Streptococcus bovis (lutetiensis) according to microbiological culture and pathology studies. A literature review of this microorganism as a cause of osteomyelitis has been conducted. Confirmation of a case of chronic osteomyelitis of the calcaneus caused by Streptococcus lutetiensis at approximately 4 months of evolution from the initial symptomatology was obtained, and the patient was treated with surgery and antibiotics, resulting in resolution of the infection process. The AOFAS score improved from a preoperative value of 33 to 89 at 6 months after surgery. Osteomyelitis caused by Streptococcus bovis is rare and even less common in the Streptococcus lutetiensis subgroup. Level of evidence IV; Therapeutic studies - investigating the results of treatment.